METHOD OF SYNTHESIS OF MICROWAVE PASSBAND FILTERS WITH SHORTED QUARTER-WAVE STUBS - Karpukov, L. M.; Korolkov, R. U. (Radio Electronics, Computer Science, Control, 2010)
The function of filtration is entered for pass-band filters with a symmetric structure, composed of quarter-wave sections of lines and shorted stubs. The method of determination of polynomial dependences for numerators and denominator of filter dispersion parameters is developed. The method of filter sections wave resistance calculation by its scattering parameters is proposed. The example of filter calculation by the procedure realizing the proposed relationships is described.